The crystal structure of zwitterionic 2-{[(4-iminiumyl- 3-methyl-1,4-dihydropyridin-1-yl)methyl]- carbamoyl}benzoate hemihydrate - C. S., Chidan Kumar; Ai, Jia Sim; Weng, Zhun Ng; Tze, Shyang Chia; Loh, Wan Sin; Huey, Chong Kwong; Ching, Kheng Quah; S., Naveen; N. K., Lokanath; Warad, Ismail (International Union of Crystallography, 2017)
The asymmetric unit of the title compound, C15H15N3O30.5H2O, comprises two 2-{[(4-iminiumyl-3-methyl-1,4-dihydropyridin-1-yl)methyl]carbamoyl}benzoate zwitterions (A and B) and a water molecule. The dihedral angles between the pyridine and phenyl rings in the zwitterions are 53.69 (10) and 73.56 (11) in A and B, respectively. In the crystal, molecules are linked by N—H O, O— H O, C—H O and C—H (ring) hydrogen bonds into a three-dimensional network. The crystal structure also features – interactions involving the centroids of the pyridine and phenyl rings [centroid–centroid distances = 3.5618 (12) A ° in A and 3.8182 (14) A ° in B].